Strategies for Colorectal Cancer Screening - Ladabaum, Uri; Dominitz, Jason A; Kahi, Charles; Schoen, Robert E (Gastroenterology (New York, N.Y. 1943), 2020)
The incidence of colorectal cancer (CRC) is increasing worldwide. CRC has high mortality when detected at advanced stages, yet it is also highly preventable. Given the difficulties in implementing major lifestyle changes or widespread primary prevention strategies to decrease CRC risk, screening is the most powerful public health tool to reduce mortality. Screening methods are effective but have limitations. Furthermore, many screen-eligible people remain unscreened. We discuss established and emerging screening methods, and potential strategies to address current limitations in CRC screening. A quantum step in CRC prevention might come with the development of new screening strategies, but great gains can be made by deploying the available CRC screening modalities in ways that optimize outcomes while making judicious use of resources.